Isolation and identification of 3-chloropropionic acid degrading bacterium from marine spong - Mohd Sufian, Nurul Hanani; Mohamad, Mohd Azrul Naim; Tengku Abdul Hamid, Tengku Haziyamin; Huyop, Fahrul Zaman; Abdul Hamid, Azzmer Azzar (Penerbit UTM Press, 2015)
Synthetic haloalkanoic acids often applied as active components in herbicides are toxic to the environment and harmful to the living organisms. These compounds are widely released to the environment due to their routine use by agricultural activities. In recent years, accumulation of haloalkanoic acids was emerged in marine environment. In this study, a 3CP-degrading bacterium which designated as strain H4 was successfully isolated from marine sponge Gelliodes sp. that capable of degrading 3CP as the sole carbon and energy source. The bacteria growth on solid minimal media containing 3CP was the evident for the presence of dehalogenase enzyme. In liquid medium, the doubling time of the cells for strain H4 was 56.82 ± 0.1 h while the maximum chloride ion release was 2.03 ± 0.01 mM. The 16S rDNA sequence of strain H4 was obtained via 16s rRNA gene analysis (1000 bp) and it was closely related to Bacillus aryabhattai B8W22 (99% similarity). To the best of knowledge, this report is the first report detailing haloalkanoic acid degrading bacteria from marine sponge in coastal area of Malaysia.